Howler Reef - Deas, Mike, 1982-; Deas, Nancy (Deas, Mike, 1982- Sueño Bay adventures, 2025)
"In this graphic novel for early middle readers, Kay fights through her fear of kayaking to join her friends on a kids-only paddle up the coast from Sueño Bay to the Whisper Islands. But unbeknownst to the group, Kay has a secret goal: to find the missing person whose ship disappeared weeks before."--